Effects of antiviral therapy for hepatitis C following treatment of hepatocellular carcinoma: survey findings of the Japanese Red Cross Liver Study Group. Issue 4 (24th March 2015) - Joko, Kouji; Goto, Tohru; Watanabe, Hiroshi; Mitsuda, Akari; Uchida, Yasushi; Hasebe, Chitomi; Tsuruta, Shotaro; Kimura, Hiroyuki; Koike, Takero; Akamatsu, Takuji; Mashiba, Toshie; Ochi, Hironori; et al.
Abstract : Aim: To investigate, in a large number of cases at multiple institutions, the effects and limitations of antiviral therapy for hepatitis C following treatment of hepatocellular carcinoma (HCC) in clinical practice. Methods: Retrospective analysis was performed of 112 patients who had received interferon (IFN) for treating hepatitis C following treatment of HCC and were registered with the Japanese Red Cross Liver Study Group. Factors that may influence recurrence and survival rates were investigated. Results: Factors involved in prevention of recurrence were: surgical resection as HCC treatment, platelet and α‐fetoprotein (AFP) levels prior to IFN administration, IFN adherence and post‐IFN AFP level. Multivariate analysis showed post‐IFN AFP level to be an independent factor. Factors involved in prolonging survival were: IFN adherence, IFN response (sustained viral response), pre‐IFN alanine aminotransferase and AFP levels, post‐IFN AFP level and absence of recurrence. Multivariate analysis showed absence of recurrence to be an independent factor. Although IFN adherence was involved in recurrence and survival, ribavirin adherence was not. IFN was suggested to be involved in preventing recurrence and improving survival due not only to its anti‐viral effect, but also its antitumor effect. Conclusion: Although complete prevention of HCC recurrence is difficult, the most important factor affecting first recurrence is the AFP level at 6 months after the conclusion of antiviral treatment. The survival rate improves dramatically if the hepatitis C virus is eliminated, but the most important factor for improving survival is absence of recurrence.